P862 Clinical benefit potentially evident with immunopharmacodynamic responses in prior-checkpoint failed metastatic melanoma patients treated with imprime PGG and pembrolizumab. (15th April 2020) - Chan, Anissa; Bose, Nandita; Bose, Nandita; Ottoson, Nadine; Qiu, Xiaohong; Harrison, Ben; Walsh, Richard; Mattson, Paulette; Gargano, Michele; Cox, Joanna; Chisamore, Michael; Uhlik, Mark; et al.
Abstract : Background: Checkpoint inhibitor (CPI) monotherapy has revolutionized the treatment of melanoma, yet most patients are primary nonresponders or develop secondary resistance. Lack of antigen-specific T cell priming and/or immunosuppressive mechanisms leading to T cell exhaustion are critical cancer-extrinsic factors contributing to CPI resistance mechanisms. Immunotherapeutic agents capable of sparking de novo anti-tumor T cell responses or reinvigorating pre-existing exhausted T cell immunity could help reinstate the activity of CPI. Methods: Our Phase 2, multi-center, open label study, NCT02981303 in collaboration with Merck & Co., Inc., is evaluating Imprime PGG (Imprime), a novel yeast derived, Dectin-1 agonist, β-glucan PAMP in combination with pembrolizumab (KEYTRUDA®, pembro) in heavily CPI pre-treated melanoma patients (20 patients; 65% had >2 prior CPI regimens with 17/20 having previously progressed on pembro). Patients received Imprime (4 mg/kg) + pembro (200 mg) intravenously in a 3-week cycle. Here, we present the immunopharmacodynamic (IPD) responses elicited by Imprime and pembro in the peripheral blood of 19 patients. Results: In the intent-to-treat population (ITT; N=20), the disease control rate was 45% (1 CR and 8 SD), 6-month and 12-month OS rates were 65% and 45% respectively, and median OS (mOS) was 8.8 months. In the patients showing disease control, a significant increase in CH50, the classical pathway complement function (~0.7-2.6-fold), HLA-DR expression on classical monocytes (~0.61-1.94-fold) and reduction of frequency of PD-1+Tbet-EOMES+ exhausted CD8 T cells (~0.9-4-fold) was observed. Stimulation of peripheral blood mononuclear cells from a subset of patients by CD3/CD28 beads showed enhanced production of IL-2 and IFN-gamma in the CD8 T cells. Some of these IPD responses were also associated with 6-month landmark OS analyses. Additionally, whole blood gene expression analyses showed >2-fold upregulation of several myeloid and T cell activation genes including IFNg, CD83, IP-10, and IL-2RA. Enhanced OS was observed in patients with >1.3 fold increase in CH50 (8/19; HR 0.385; p=0.1) or >1.5-fold reduction in the frequency of exhausted CD8 T cells (8/19; HR 0.102; p=0.001). The IPD responses observed in the ITT population included formation of circulating immune complexes (peak levels ranging from ~4.5-16.1-fold) and production of complement activation protein SC5b9 (~3.4-25.6-fold), and increase in the frequency of HLA-DR+ myeloid cells (~0.43-3.71-fold). Conclusions: Overall, these data, albeit in a small population, demonstrate that Imprime/pembro combination can drive the innate/adaptive IPD responses that are critical for providing clinical benefit to the patients who have progressed through prior CPI treatments. Ethics Approval: The study was approved by central and local ethics committees depending on site requirements. The central IRB for the study is Western Institutional Review Board (WIRB), approval number 20162506; all sites received IRB approval before opening the study at the respective sites.